2013
DOI: 10.1007/s11524-013-9850-7
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Heat Awareness and Protective Behaviors in New York City

Abstract: Heat waves can be lethal and routinely prompt public warnings about the dangers of heat. With climate change, extreme heat events will become more frequent and intense. However, little is known about public awareness of heat warnings or behaviors during hot weather. Awareness of heat warnings, prevention behaviors, and air conditioning (AC) prevalence and use in New York City were assessed using quantitative and qualitative methods. A random sample telephone survey was conducted in September 2011 among 719 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
5
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 20 publications
(24 reference statements)
6
90
5
5
Order By: Relevance
“…Overheating has been observed across Europe and in North America (e.g., Lane et al, 2014;Lee & Shaman, 2016), but in this issue the majority of the papers, eight in all, are from UK researchers, which is illustrative of the rising level of concern about overheating in many places with a temperate climate. Seven papers report monitoring studies conducted between 2009 and 2015 in dwellings covering the entire nation.…”
Section: Why Is Overheating a Problem And Why Now?mentioning
confidence: 95%
“…Overheating has been observed across Europe and in North America (e.g., Lane et al, 2014;Lee & Shaman, 2016), but in this issue the majority of the papers, eight in all, are from UK researchers, which is illustrative of the rising level of concern about overheating in many places with a temperate climate. Seven papers report monitoring studies conducted between 2009 and 2015 in dwellings covering the entire nation.…”
Section: Why Is Overheating a Problem And Why Now?mentioning
confidence: 95%
“…There is considerable evidence that confirms the importance of demographic characteristics (Haque et al, 2012; Semenza et al, 2008; Wolf et al, 2010), previous personal experience of extremes (Spence et al, 2011; Howe et al, 2013; Liu et al, 2013), amount of information given, and exposure to extreme temperatures in affecting extreme heat and cold temperature perception in individuals of developed countries (Lindell and Hwang, 2008; Liu et al, 2013; Wachinger et al, 2013; Wei et al, 2014). An Australian study suggested that age, household income, living arrangement, and fan ownership were significant predictors of perception on extreme heat related health risk (Akompab et al, 2013), and these factors also have had impacts on extreme heat awareness in New York City (Lane et al, 2013). In Europe, previous personal experience of extreme weather events, such as flood (Spence et al, 2011) and extreme cold temperatures (Capstick and Pidgeon, 2014; Wolf et al, 2010) could significantly impact public recognition on and against climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding within-city vulnerability can help guide efforts to prevent heat-related deaths, including urban planning measures that apply susceptibility and exposure information to prioritize urban heat island reduction efforts, public messaging during heat waves, and provision of air conditioners and electric power subsidies (Lane et al , 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…A recent telephone survey indicated that approximately 11% of New Yorkers do not have a functioning air conditioner, and an additional 14% do not use their air conditioner regularly (Lane et al ., 2013b). The most frequently cited reason for lack of air conditioning ownership was cost, followed by the perception that it was not needed and a dislike of air conditioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation